Hubungan Penggunaan Hastag #Samasamabelajar Melalui Media Tiktok Terhadap Kebutuhan Informasi Mahasiswa Ilmu Perpustakaan Semester 7 - Nursawiyah; Abdul Karim Batubara (EduInovasi: Journal of Basic Educational Studies, 2025)
The internet in the digital era has become important in everyday life. It has become a familiar thing when people spend more of their time doing online activities. The features contained in social media are also increasingly diverse. One of them is the hashtag symbol or in English is Hashtags (#). to determine the relationship between the use of the hashtag #samasamabelajar and the information needs of 7th semester library science students. In this research, researchers used quantitative research with a cross-sectional design. Where the data collected will be processed using SPSS. The population is 400 7th semester library science students who use Tiktok at the Faculty of Social Sciences, North Sumatra State Islamic University with a total sample of 50 people. The results of this research are that there is a relationship between the use of #samasamabelajar via TikTok social media and the information needs of 7th semester library science students students. With p value = 0.000. Conclusion: The hashtag #samasamalearn can be used and is very useful for students in finding the information they need, especially in learning various things.